GROWTH PERFORMANCE, YIELD COMPONENT AND GENOTYPIC RESPONSE OF MUNGBEAN (VIGNARADIATA L.) AGAINST SOIL BORNE DISEASES - Uge, Emerensiana; Iswanto, Rudi; Hapsari, Ratri Tri; Trustinah, Trustinah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Soil-borne disease caused by fungus infection is one of the disease that causes the death and crop failure of mungbean. The aim of this study was to identify the performance, yield component and respons of plant to the disease. Performance of 25 genotypes were observed in installations research and assessment of agriculture technology (IPPTP), Jambegede of Indonesian Legumes and Tuber Crops Research Institute (ILETRI)at dry season 2018 using RCBD with three replications. The result showed that each variety has different characteristic. The plant with the highest number of plant height was genotype 15 and 18, while the total branches of 25 genotypes were generally similar (4).The highest number of grown and harvested plant was genotype 15. The genotypes with shorter flowering, maturity and harvesting age were 23, 20, 18, 15 and 10. The highest average number of filled pods was genotype 11 and empty pods was genotype 13. There were 8,10 and 2 genotypes with seeds weight of >7, >6 and <6 respectively. The highest yields were obtained from genotype 19 and 3 by total of yield of 2.0 t/ha and 1,9 ton/ha respectively. Resistance test against soil-borne diseases resulted 5 genotypes that were moderate resistant observed at 2 DAP. This research contributed to gave information about new genotypes of mungbean that potentially produce new superior varieties.